Treatment of obesity - A review through the eyes of a primary care physician - Hanna Porwolik,; Agnieszka Porwolik,; Magdalena Bodera,; Radoslawszdlowski,; Dominik Rabstein,; Piotr Gosciniewicz,; Marek Skotarski, (Pakistan Journal of Medical & Health Sciences, 2024)
Aim: To provide primary care physicians with a comprehensive knowledge of non-pharmacological, pharmacological and surgical treatments for obesity, increasing the effectiveness of obesity treatment in primary care settings. Methods: Pubmed and Google Scholar databases, magazine Practical Medicine and WHO page were searched using the keywords: "obesity", "pharmacological treatment of obesity", "non-pharmacological treatment of obesity", "bariatric surgery". We then analyzed a selection of material. Non-pharmacological methods, such as diet, physical activity and psychological support, are the cornerstone of obesity treatment. Results: Pharmacological treatment includes combinations of naltrexone and bupropion, liraglutide, semaglutide and orlistat, used when non-pharmacological interventions do not have the desired effect. Bariatric surgery, which is effective for severe obesity, includes procedures such as LSG and LRYGB, which are highly effective in reducing weight and treating comorbidities. Conclusion: Successful obesity treatment requires a multifaceted approach combining non-pharmacological, pharmacological, and surgical methods. Semaglutide, the most effective drug, aids weight loss and improves metabolic parameters. Bariatric surgery is most effective for grade 3 obesity but necessitates careful patient selection and post-surgery dietary adherence Keyword: Obesity; overweight; family doctor; primary care physician